Fluorescein Isothiocyanate (FITC)‐Dextran Extravasation as a Measure of Blood‐Brain Barrier Permeability. Issue 1 (10th April 2017) - Natarajan, Reka; Northrop, Nicole; Yamamoto, Bryan
Abstract: The blood‐brain barrier (BBB) is formed in part by vascular endothelial cells that constitute the capillaries and microvessels of the brain. The function of this barrier is to maintain homeostasis within the brain microenvironment and buffer the brain from changes in the periphery. A dysfunction of the BBB would permit circulating molecules and pathogens typically restricted to the periphery to enter the brain and interfere with normal brain function. As increased permeability of the BBB is associated with several neuropathologies, it is important to have a reliable and sensitive method that determines BBB permeability and the degree of BBB disruption. A detailed protocol is presented for assessing the integrity of the BBB by transcardial perfusion of a 10, 000 Da FITC‐labeled dextran molecule and its visualization to determine the degree of extravasation from brain microvessels. © 2017 by John Wiley & Sons, Inc.